Effect of plyometric training on speed parameters (A meta-analysis study) - Söyler, M.; Kayantas, I. (International Journal of Applied Exercise Physiology, 2020)
The basic purpose of this study is to combine the results of studies on the effect of plyometric training on speed in different places and times and to reveal the overall effect sizes of these results. For this purpose; 2000-2020 year include plyometric training methods of influence on the subject of studies on the speed parameter in Turkey The Council of Higher Education of the National Thesis Archive, Google and academic journals park website published postgraduate theses and research articles on their sites handled the work which fulfilled the criteria for inclusion of studies It was obtained. Studies that do not meet the specified criteria are excluded from our research. For studies with higher heterogeneity values than normal, moderator analyzes of variables such as age, training period, sports branch and publication type were performed. Comprehensive Meta-Analysis (CMA) program was used for experimental meta-analysis. According to the results of the meta-analysis data of this study, the effect of plyometric training on the speed property is 0,721 in the fixed effects model for the 10 meter speed feature; in the random effects model, it has a medium level of 0,724 effectsize, and 0,676 in the fixed effects model for 20 meters speed; It has been determined that it has medium effect size with 0,725 effect size in random effects model, 0,574 in fixed effects model for 30 meters speed feature, and medium effect size with 0,645 effect size in random effects model. According to the results of this study, it can be said that plyometric training is moderately effective for the development of speed feature.